CHANGES IN WEIGHT AND BODY MASS INDEX OF PATIENTS UNDERGOING HYRAX EXPANDER THERAPY - Shah, Ahsan Mehmood; Shabir, Sundus; Khan, Kiran; Saood, Muhammad; Ali, Farhad; Yousufi, Siddiq (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the changes in weight and body mass index of patients with a Hyrax expander in one month and three months after cementation. Methodology: A total of 130 patients from 10-14 years of age with an indication of Hyrax expander were included in this quasi-experimental study. Patients were enrolled through the convenience sampling technique. The study was carried out from November 2019 to January 2022 at the Department of Orthodontics, Khyber College of Dentistry, Peshawar. The Height and weight were measured at 3-time intervals; T0 (before initiation of treatment), T1 (1 month after appliance cementation), and T2 (3 months after appliance cementation). Data analysis was done using IBM SPSS 25.0. The body mass index at T0, T1, and T2, along with means, standard deviations, frequencies, and percentages, were calculated. A paired samples t-test was employed to check the mean differences in weight and body mass index at T0, T1, and T2. A p-value of <0.05 was considered significant. Results: The mean age of 130 patients was 11.81 ± 1.31 years. The number of male patients were 54 out of 130 and female patients were 76 out of 130. The mean difference in weight loss at T0-T1 (0.83 kg ±2.69) was statistically significant.(p =0.001) So was the mean difference of body mass index (0.43 kg/m2 ± 0.81) at T0-T1. The mean differences in both weight and body mass index were insignificant at T2. Conclusion: A decrease in body mass index and weight loss is observed in patients undergoing hyrax expander therapy 1 month after initiation of treatment.